Get Shorty. Season one [videorecording (DVD)]. - Romano, Ray; O'Dowd, Chris, 1980-; Dodd, Carolyn; Leonard, Elmore, 1925-2013 (20th Century Fox Home Entertainment, 2018)
The story of Miles Daly who works as muscle for a murderous crime ring in Nevada and attempts to change professions and become a movie producer, laundering money through a Hollywood film.